Employment relationships of Chinese expatriates: A multi-foci perspective of psychological contract - Wang, Xiao; Wang, Siming; Zhu, Mengmei (Frontiers in Psychology, 2023)
Research into expatriation has made a great contribution to the understanding of issues surrounding international human resource management. However, academic discussion around the subject of expatriate management remains Western-centred, neglecting the use of expatriate staffing in multinational corporations (MNCs) from Eastern countries. By adopting a multi-foci perspective of the psychological contract, the overall objective of this research is to explore the content of Chinese expatriates’ psychological contracts. This paper draws on the findings of an organisational case study and is based on semi-structured interviews with 14 expatriates. Overall, the findings provide evidence that individuals have multiple simultaneous psychological contracts, each with a different focus. The contracts held by the Chinese expatriates in this sample contain predominately balanced contract beliefs, which contrast sharply to what the other authors find to be salient beliefs (e.g., transactional contract beliefs) for expatriates based on Western samples. Importantly, the most frequently listed exchange partners by the pre-departure expatriates were line managers and department managers in headquarters; individuals appreciate the respective role of each party in shaping their aspects of work conditions whilst acknowledging the simultaneous existence of such influences. This paper has implications for expatriate management in the following ways. First, managers are encouraged to appreciate the role of multiple parties in shaping expatriates’ psychological contracts. This helps to enhance management’s understanding on the motives and demands of those expatriates. Second, policies of support and contact would aid feelings of integration. Finally, more attention should be paid to planning expatriate career prospects.